Soil organic carbon content and soil structure quality of clayey cropland soils: A large‐scale study in the Swiss Jura region. (4th February 2023) - Johannes, Alice; Sauzet, Ophélie; Matter, Adrien; Boivin, Pascal
Abstract: Soil organic carbon (SOC) fashions soil structure, which is a key factor of soil fertility. Existing SOC content recommendations are based on SOC:clay ratio thresholds of >1:10. However, the corresponding SOC content might be considered hard to reach in clayey soils, whose structure degradation risk is assumed to be high. Here, we analysed the SOC content and soil structure quality of soils under similar cropping practices with clay contents ranging from 16% to 52%. Five undisturbed soil cores (5–10 cm layer) were collected from 96 fields at 58 farms in the Swiss Jura region. We assessed the soil structure quality visually using the CoreVESS method. Gravimetric air content and water content, and bulk density at −100 hPa were also measured, and the soil structure degradation index was calculated. We found that the relationship between SOC and clay content held over the clay content range, suggesting that reaching an acceptable SOC:clay ratio is not limited by large clay contents. This suggests that the 1:10 SOC:clay ratio may remain useful for clayey soils. In contrast to what was expected, it is not more challenging to reach this ratio in clayey soils even if it implies reaching very large SOC contents. SOC content explained the considered physical properties better than clay content. From a soil management point of view, these findings suggest that the soil texture determines a potential SOC content, while the SOC:clay ratio is determined by farming practices regardless of the clay content.